PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH SUSU SAPI PERAH DI KABUPATEN BOYOLALI PROVINSI JAWA TENGAH - Dimas Novendra Alfianto; Rossy Lambelanova (ipdn, 2021)
Boyolali Regency is a Regency with a cattle population and the largest producer of meat and milk in Central Java. However, the abundance of potential resources has not been utilized optimally by Micro, Small and Medium Enterprises (MSMEs). Given this phenomenon, the role of the government through the Department of Cooperatives and Manpower of Boyolali Regency has an important task of empowering dairy cow milk SMEs in maximizing the existing potential and then using it to improve welfare. The purpose of this study was to analyze how the implementation of MSME empowerment carried out by the Boyolali District Cooperatives and Manpower Service, to find out the inhibiting factors of the empowerment program, and to analyze the efforts made by the Boyolali District Cooperatives and Manpower Service in increasing the productivity of dairy cows MSMEs. This research method is a descriptive qualitative research design with a deductive approach. The data collection technique used in this research is through the results of interviews, observation and documentation. Data analysis was carried out using the stages of empowerment, namely awareness and behavior formation activities, transforming knowledge and skills, and carrying out intellectual ability enhancement. The results of this study indicate that the implementation of the dairy cow's milk MSME empowerment program in Boyolali Regency has been running well, but there are still several obstacles including the lack of product development innovation, the nature of cow's milk that is easily spoiled making processing difficult, and limited funds causing disruption of empowerment. It is recommended to carry out the empowerment process by: Continuous or sustainable guidance or assistance by relevant stakeholders, adjustment of training time, training carried out offline and online, creation of business partners or associations, ease and facilitation of business licensing, utilizing information technology to expand marketing networks. Keywords: UMKM, Empowerment, Welfare